The impacts of nanoscale silica particle additives on fuel atomisation and droplet size in the internal combustion engines: A review - Balikowa, Amuza; Effendy, Marwan; Ngafwan, Ngafwan; Wandera, Catherine (Universitas Muhammadiyah Surakarta, 2023)
The combustion process in compression ignition (CI) engines is complex and affects their efficiency and emission levels. Internal combustion engines (ICE) are being studied to find better ways to burn fuel and produce less pollution to meet the growing demand for these qualities. However, one intriguing avenue is the utilisation of nanoparticle additives, such as silica nanoparticles, to enhance fuel atomisation and droplet size. This study aimed to comprehensively review the impact of silica nanoparticle additives on fuel atomisation and droplet size in internal combustion engines. This review explores the researchers' underlying mechanisms and experimental techniques to determine nanoparticle fuel additives' overall impact on engine performance. The results achieved from the literature study indicated that incorporating these nanoparticles (following the engine design and fuel formulations) can enhance combustion efficiency and reduce exhaust emissions, thereby contributing to developing more sustainable transportation and power production systems.